2006
DOI: 10.1002/pds.1351
|View full text |Cite
|
Sign up to set email alerts
|

Hospitalisations and emergency department visits due to drug–drug interactions: a literature review

Abstract: This review provides information on the overall incidence of D-DIs as a cause of adverse patient outcomes, although there is still uncertainty about the impact of D-DIs on adverse patient outcomes. Our results suggest that a limited number of drugs are involved in the majority of cases and that the number of reasons for admission as a consequence of D-DIs seems to be modest.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

7
217
1
12

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 263 publications
(237 citation statements)
references
References 30 publications
7
217
1
12
Order By: Relevance
“…The presence within the kidney of this common pathway for the secretion of OCs sets the stage for unwanted drug-drug interactions (DDIs) (Lepist and Ray, 2012). The clinical cost of DDIs is substantial and responsible for approximately 1% of hospital admissions (almost 5% in elderly populations) [Becker et al, 2007; U.S. Food and Drug Administration, Preventable adverse drug reactions: A focus on drug interactions (http://www.fda.gov/Drugs/DevelopmentApprovalProcess/ DevelopmentResources/DrugInteractionsLabeling/ucm110632. htm)]; therefore, the ability to predict potential DDIs could lead to decreased morbidity and increased monetary savings.…”
Section: Introductionmentioning
confidence: 99%
“…The presence within the kidney of this common pathway for the secretion of OCs sets the stage for unwanted drug-drug interactions (DDIs) (Lepist and Ray, 2012). The clinical cost of DDIs is substantial and responsible for approximately 1% of hospital admissions (almost 5% in elderly populations) [Becker et al, 2007; U.S. Food and Drug Administration, Preventable adverse drug reactions: A focus on drug interactions (http://www.fda.gov/Drugs/DevelopmentApprovalProcess/ DevelopmentResources/DrugInteractionsLabeling/ucm110632. htm)]; therefore, the ability to predict potential DDIs could lead to decreased morbidity and increased monetary savings.…”
Section: Introductionmentioning
confidence: 99%
“…In 2007, a meta-analysis of 23 clinical studies from around the world revealed that drug-drug interactions (DDIs) cause approximately 0.054% of emergency room visits, 0.57% of hospital admissions, and 0.12% of rehospitalizations [7]. There are 136.1 million emergency room visits [8] Aim: To detect potential drug-drug interactions among medications received by hypertensive patients.…”
Section: Introductionmentioning
confidence: 99%
“…For instance, drug interactions, especially with medications having a narrow therapeutic range, may have serious adverse outcomes. A literature search in Medline and Embase database from 1990 to 2006 illustrated that drug-drug interactions (DDIs) were detained accountable for 0.054 % of the emergency department (ED) visits, 0.57 % of the hospital admissions, and 0.12 % of the re-hospitalizations (Becker et al, 2007). It is conceivable that medication connection can be helpful or hindering.…”
Section: Introductionmentioning
confidence: 99%